(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The evaluation of flat shallow cavity solar collector inserted with porous substrate was investigated experimentally and numerically. The aim of this work is to improve the thermal performance of flat plate solar collectors using enhanced heat transfer technique. Porous media were made of multilayer of aluminum mesh to form a porous layer of thickness 25 mm inserted under the absorber plate with porosity of 0.9 and permeability of 84.87. The solar collector was installed in Baghdad south facing at a fixed tilt angle (45°). Three types of solar collector have been designed and constructed namely solar collector made of shallow enclosure (model I), solar collector made of shallow enclosure inserted partially with porous layer (model II) and solar collector with channels of corrugated channels inserted partially with porous layer (model III). The results of parametric study of model III in case of continuous operating showed that the maximum average water temperature difference of water between collector outlet and inlet exceeds (7.21°C) and the maximum outlet temperature exceeds (50°C) at solar noon for (November, and December 2013). The thermal efficiency for collector model III was ranged from 47.52% to 52.2%, while that for model I was ranged (33.5% to 42.3%) under the same environmental conditions.